Referral of students with disabilities to Special Education services in Manaus: what are the criteria? - Galvani, Márcia Duarte (2020)
This study aimed at the referral session of students with disabilities to the Special Education services in the Manaus. This is a descriptive study, using interview techniques and documentary research. It was used as a scripted interview instrument for four teachers (P1, P2, P3 and P4) and a representative of the Special Education Management (P5). The documentary research was carried out in a municipal education published between 1991 and 2017. The results pointed out that the sending of data to the education services was special throughout 1991 and 2017. The clinic aimed at pedagogical perspective and human rights. The criteria for identification, assessment and referral of students with disabilities need to be delineated, taking into account the specificities of the students and a question of law.